Power Relation in English Classroom: A Case Study in Teaching Assistance of MBKM Program - Denny Kodrat (Siliwangi University, 2021)
Indonesia Ministry of Education has launched Merdeka Belajar Kampus Merdeka (MBKM). One of the programs selected by university students is teaching assistance at schools. The study is investigated how the university student, as a teacher assistant, deals with teaching methods promoting critical thinking and problem solving and designing student center teaching activities. Critical thinking and problem solving and a student center are 21st-century students’ life skills that should be embedded in teaching. The study used a qualitative approach with a case study method. This approach is aimed at uncovering power relations in the English classroom. The researcher becomes a key instrument who cannot be delegated. The finding then is sufficiently reconstructed by keeping a natural setting, so the finding data can be depicted as the aims of the research are expected. The study was conducted at MBKM program by the English Literature Study Program, STBA Sebelas April Sumedang. In-depth observation and interview on teaching activities in the classroom and teaching documents (lesson plan) examination were performed toward a university student teaching English. The data finding then is interpreted by the Critical Discourse Analysis theory suggested by Fairclough (2001). The result shows that a teacher is dominant in teaching English, making students difficult to expose their critical thinking and problem-solving skills, collaboration, communication, and creativity. Keywords : power, cda, domination, critical thinking, mbkm